Marketing Communication of the Baduy People in Increasing Tourist Visits for Economic Recovery Post Covid-19 Pandemic - Ram, Mutia Putri Sani; Yuliasari, Ika; Elizabeth, Novianty (Jurnal Dakwah dan Komunikasi, 2024)
Craftsmen of various typical Baduy products have experienced a decline in income since the Covid-19 pandemic. In the first year of the pandemic, visits to Baduy were still relatively high with 20,319 local tourists and 8 foreign tourists in 2020. Then visits shrank to 6,274 tourists throughout 2021. This article aims to see how marketing communications are applied in a more effective effort to increase tourist visits to recovery using a social phenomena approach with qualitative analysis. The results found show that an integrated approach, combining soft selling and hard selling, has succeeded in improving the economy of the Baduy community by increasing the number of visitors by 22%, especially in the context of revitalizing their traditional weaving industry. The pattern of interaction developed by the Baduy community towards tourists is active interaction, either face to face or in groups, where storytelling about Baduy culture and historical values attracts tourists in buying souvenirs and natural products from the Baduy community.